Grass carp STK38 regulates IFN I expression by decreasing the phosphorylation level of GSK3β. (October 2019) - Xu, Kang; Xie, Xiaofen; Qi, Guoqin; Weng, Panwei; Hu, Zhizhen; Han, Kun; Yuan, Huiwen; Li, Yinping; Ran, Xiaoqin; Lin, Gang; Hu, Chengyu
Abstract: As a member of NDR protein kinase family and a novel protein kinase of Hippo signal pathway, Serine/threonine kinase 38 (STK38) plays a very significant role in the innate immune. In mammals, STK38 performs its function by combining with GSK3β. Nowadays, there are few reports of STK38 in fish. In order to explain the function of fish STK38 in the innate immunity, we cloned the ORF of grass carp ( Ctenopharyngodon idella ) STK38 ( Ci STK38) and the related kinase GSK3β ( Ci GSK3β). Phylogenetic trees revealed that Ci STK38 and Ci GSK3β evolved closer kinship with sinocyclocheilus grahami STK38 and siniperca chuatsi GSK3β respectively. CiSTK38 and CiGSK3β can respond to the intradermal injection of poly (I:C) in grass carp different tissues and the transfection of poly I:C in CIK cells. Subcellular localization revealed the CiGSK3β were broadly distributed through the cytoplasm, whereas CiSTK38 were observed both in cytoplasm and nucleus. However, when they were co-transferred into cells, the two proteins were found to aggregate in the nucleus. GST-pulldown and co-immunoprecipitation analysis revealed that CiSTK38 can physically interact with CiGSK3β. Phos-tag PAGE illustrated CiSTK38 can decrease the phosphorylation and auto-phosphorylation level of CiGSK3β at Ser9 and at Tyr216. To investigate the functional correlation between CiSTK38 and CiGSK3β, we overexpressed CiSTK38 and CiGSK3β in CIK cells and found that they can up-regulate the expression of IFN I . In short, we demonstrated that CiSTK38 can confer CiGSK3β kinase activity by reducing its phosphorylation level. Result from this study strongly suggested that the anti-viral immune effects elicited by poly (I:C) in part were mediated through activation of CiGSK3β. The findings provided scientific basis for the anti-viral immune mechanism of STK38 and GSK3β in fish. Highlights: CiSTK38 and CiGSK3β respond to poly I:C stimulation. CiSTK38 can physically bind to CiGSK3β in the absence of poly I: C. CiSTK38 activates CiGSK3β via promoting its dephosphorylation. CiSTK38 promotes the expression of IFN I via CiGSK3β.